Efeito do pó de casca de noz pecan nas propriedades de bandas de rodagem de pneus - Abatti, Lisandra (My University, 2019)
The use of natural organic materials in polymer products has attracted great attention in recent years due to economic, environmental and reduction dependence on petroleum based products. In this context, this work aims to substitute part of the carbon black for pecan nutshell in rubber compositions for application in tire treads. Pecan nutshell, composed on cellulose, hemicellulose and lignin, which is renewable, was obtained from the local's rural producers, and were ground and dried in an oven to 1% moisture. In the first stage of the study, formulations were evaluated by substituting part of the carbon black for 5, 10, 20, 40 and 50 phr of pecan nutshell powder and compared with a formulation only with carbon black. The results of dynamic-mechanical analysis (DMA) show that the nutshell powder raises tan  at 0 °C by up to 6%, favoring the wet traction. Through the tests of oxidation induction time (OIT) it is observed that the pecan nutshell powder promotes excellent antioxidant properties. In the second step of the study, were selected the formulations with better properties (5 and 10 phr of nutshell), and was added silane tetrasulphate bis (triethoxysilylpropyl) (TESPT) in proportions of 10 and 20% in order to promote better compatibility between the nutshell powder and the elastomeric matrix. The results obtained in DMA demonstrate that the use of TESPT improve fuel economy and wet traction, and also provides improvement in all of the physico-mechanical properties of the formulations.
A utilização de materiais orgânicos naturais em produtos poliméricos tem atraído grande atenção nos últimos anos por questões econômicas, ambientais e por reduzir a dependência dos derivados do petróleo. Neste contexto, este trabalho tem como objetivo substituir parte do negro-de-fumo por pó de casca de noz-pecan em composições de borracha para aplicação em bandas de rodagem de pneus. As cascas de nozes, obtidas dos produtores rurais da região, possuem uma composição baseada em celulose, hemicelulose e lignina, foram moídas e secas em estufa até umidade 1%. Na primeira etapa do estudo foram avaliadas formulações substituindo-se parte do negro-de-fumo por 5, 10, 20, 40 e 50 phr de pó de casca de nozes e comparada com uma formulação somente com negro-de-fumo. Os resultados de análise dinâmico-mecânica (DMA) demonstram que o pó de casca de nozes eleva a tan  a 0 °C em até 6%, favorecendo a frenagem no molhado. Através dos testes de tempo de indução a oxidação (OIT), observa-se que o pó de casca de nozes promove excelentes propriedades antioxidantes. Na segunda etapa do estudo, foram selecionadas as formulações com melhores propriedades (5 e 10 phr de casca de nozes), e utilizou-se o agente de acoplamento Tetrasulfeto bis(trietoxisililpropil) (TESPT) nas proporções de 10 e 20%. Os resultados obtidos no DMA demonstram que o uso de TESPT promove economia de combustível através da redução na resistência ao rolamento, melhora a frenagem no molhado e favorece as propriedades físico-mecânicas das formulações.
Keywords: Materiais - Testes; Borracha; Automóveis - Pneus; Nogueira-pecã; Cascas; Materials Testing; Rubber; Automobiles Tires; Pecan tree; Bark